Quality management and supply chain management integration: a conceptual model - Fernandes, Ana Cristina (2014)
Recent trends in the business world has forced companies to expand their activities into new regions where they can find qualified manpower, lower production costs, high availability of raw materials giving rise to wider and more complex supply chains but also bringing in new opportunities to leverage their competitive advantages. These changes require the implementation of new organizational models with different suppliers and partners responsible for an important part of the final product and consequently to provide a service of excellence to satisfy customers. In order to produce value and optimize profitability, it is fundamental to establish successful partnerships with the supply chain organizations that can be achieved by new models of cooperation, improved communication and integration among all the supply chain partners. The use of advanced management practices is essential to accomplish these objectives. In this context, the use of integrated approaches to quality management, logistics and SCM becomes fundamental. Therefore, it will be important to take advantage of TQM and SCM synergies in order to improve customer satisfaction, increase employee´s motivation and to promote performance of the organization. In this paper, a conceptual model is presented which reflects the integration of SCM/QM and their impact in companies’ performance.